Genetic Predisposition to Primary Lactose Intolerance Does Not Influence Dairy Intake and Health-Related Quality of Life in Romanian Children: A Hospital-Based Cross-Sectional Study - Corina Pienar; Liviu Pop; Marilena Lăzărescu; Radmila Costăchescu; Mirela Mogoi; Ruxandra Mare; Edward Șeclăman (MDPI AG, 2023)
Background: Primary lactose intolerance (PLI) is characterized by the inability to digest lactose. Homozygotes for the lactase gene polymorphisms (CC or GG) are considered to be genetically predisposed to PLI. Still, symptoms may only be present later in life. The evidence supporting a link between PLI, dairy intake, and quality of life (QoL) is limited in children. Aim: This study investigates the link between LCT polymorphisms and suggestive symptoms and the influence of the genetic predisposition to PLI on dairy intake and QoL in Romanian children. Materials and methods: We recruited consecutive children evaluated in our ambulatory clinic. We asked all participants to complete a visual-analog symptoms scale, a dairy intake, and a QoL questionnaire. We used strip genotyping to identify genetic predisposition to PLI. Results: 51.7% of children had a CC genotype, and 34.5% also had a GG genotype. Most children reported no or mild symptoms. Dairy intake and QoL were similar across study groups. Conclusions: Our study shows that genetic predisposition does not necessarily assume the presence of specific symptoms. Genetic predisposition to PLI did not lead to dairy avoidance, nor did it negatively influence our children's QoL.